Enhancing academic writing pedagogy for university students in the AI age: Insights from a Delphi-based framework - Fahrus Zaman Fadhly; Dadang Solihat; Marwito Wihadi; Taufiqulloh Taufiqulloh; Umar Fauzan; Nanan Abdul Manan; Nur Fathiyya Zahira Mujahidah (Studies in English Language and Education, 2026)
Academic writing is an essential skill for university students, but many find it challenging due to problems with coherence, argumentation, and genre. These problems are multidisciplinary and are exacerbated in multilingual educational settings. In response to these concerns and issues, this research adopted a Delphi-based approach to identify, assess, and validate best teaching strategies in Academic Writing. A Delphi method was used to determine the most successful teaching methods, moderated by a panel of 15 professionals specializing in academic writing. The verified approaches derived from this approach comprised process-oriented writing instruction, computer-based writing support, genre-based instruction, and metacognitive orientation training. A pilot study with 120 undergraduate participants was conducted to assess the feasibility of these expert-endorsed guidelines. Writing performance across aspects was significantly improved in the study, including coherence, argument development, lexical complexity, and overall organization (p < 0.001). Students reported highly positive perceptions of the modified teaching structure, with 87% favoring iterative writing and feedback and 79% citing benefits of AI technology; however, students also indicated a possible overreliance on technology. This paper demonstrates an integrated approach that incorporates the structural writing process, reflective learning, and digital development systems to enhance clarity, consistency, and efficiency in academic writing. Through students’ experience, this workplace validation has led to a malleable, adaptable model for enhancing pedagogy that can be applied across different university settings and serve the interests of students, curriculum design, and policymakers.